Damage Mechanism Analysis of High Field Stress on Cascode GaN HEMT Power Devices - Shuo Su; Yanrong Cao; Weiwei Zhang; Xinxiang Zhang; Chuan Chen; Linshan Wu; Zhixian Zhang; Miaofen Li; Ling Lv; Xuefeng Zheng; Wenchao Tian; Xiaohua Ma; et al. (Micromachines)
A series of problems, such as material damage and charge trap, can be caused when GaN HEMT power devices are subjected to high field stress in the off-state. The reliability of GaN HEMT power devices affects the safe operation of the entire power electronic system and seriously threatens the stability of the equipment. Therefore, it is particularly important to study the damage mechanism of GaN HEMT power devices under high field conditions. This work studies the degradation of Cascode GaN HEMT power devices under off-state high-field stress and analyzes the related damage mechanism. It is found that the high field stress in the off-state will generate a positive charge trap in the oxide layer of the MOS device in the cascade structure. Moreover, defects occur in the barrier layer and buffer layer of GaN HEMT devices, and the threshold voltage of Cascode GaN HEMT power devices is negatively shifted, and the transconductance is reduced. This study provides an important theoretical basis for the reliability of GaN HEMT power devices in complex and harsh environments.